Penguatan Kompetensi Guru PAUD sebagai Terapis melalui Stimulasi Sensori - Atika Permata Sari; Sugiarti, Sugiarti; Kumalasari, Aulia Indira; Fitriati, Sulivan (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
One concrete step taken to support SDGs 4 is the promotion of inclusive schools starting from the early childhood education (PAUD) level. However, the practice of inclusive education faces quite a number of challenges, one of which is related to sensory issues in early childhood. Teachers, as one of the important figures, play a major role in optimizing children's sensory processes through classroom activities. The community service program aims to improve teacher competency in identifying and stimulating sensory processing in early childhood. The community service activity with the main theme "Strengthening the Competence of Early Childhood Education Teachers as Therapists" was attended by 30 PAUD teachers from three inclusive kindergartens in Malang. The activity was conducted in three meetings covering basic material, material reinforcement and planning sensory stimulation, and mentoring sensory stimulation. In general, the community service program was proven effective in improving teacher competency and attitudes related to sensory issues in early childhood (p<0.01). The method that focuses on learners and strengthening skills is a major advantage of this community service. Future community services are expected to consider the sustainability of the program that has been implemented so that it can provide long-term benefits.